IMPLEMENTING ARTIFICIAL INTELLIGENCE IN THE BEAUTY INDUSTRY: INNOVATIVE APPROACHES TO PERSONALIZATION AND OPTIMIZATION OF MANICURE SERVICES - Anel Barat (American Journals, 2025)
Today, artificial intelligence (AI) is having a significant impact on the development of the beauty industry, including manicures. This article examines innovative approaches to personalizing and optimizing manicure services using AI. Current trends and examples of AI implementation in nail salons are analyzed, and the prospects and challenges associated with integrating AI into this field are discussed.
Keywords: Artificial intelligence, beauty industry, manicure, personalization, optimization, innovation.